2012
DOI: 10.1248/bpb.35.650
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Benzylisoquinoline Alkaloid Productivity by Overexpression of 3′-Hydroxy-<i>N</i>-methylcoclaurine 4′-<i>O</i>-Methyltransferase in Transgenic <i>Coptis japonica</i> Plants

Abstract: Coptis japonica (Cj) rhizomes are used as a crude drug for gastroenteritis, since they accumulate antimicrobial berberine. Berberine also shows various useful bioactivities, including cholesterol-lowering activity. Unfortunately, Cj is a slow-growing plant and more than 5 years are required to obtain a crude drug suitable for the Japanese Pharmacopoeia. To improve alkaloid productivity, we overexpressed the 3′-hydroxy-N-methylcoclaurine 4′-O-methyltransferase (4′OMT) gene in Cj. We established the transgenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…For example, the overexpression of C. japonica SMT and 4′OMT using a strong constitutive promoter, Cauliflower mosaic virus 35S, led to an increase in berberine production in C. japonica cells and plants, respectively. 39,40) Similarly, heterologous overexpression of C. japonica 6OMT improved the level of alkaloid productivity in E. californica cells. 41) It is important to note, however, that the overexpression of a biosynthetic enzyme does not always result in a successful increase in the levels of alkaloid production.…”
Section: Clarification Of the Molecular Basis Of The Iqa Biosyntheticmentioning
confidence: 93%
“…For example, the overexpression of C. japonica SMT and 4′OMT using a strong constitutive promoter, Cauliflower mosaic virus 35S, led to an increase in berberine production in C. japonica cells and plants, respectively. 39,40) Similarly, heterologous overexpression of C. japonica 6OMT improved the level of alkaloid productivity in E. californica cells. 41) It is important to note, however, that the overexpression of a biosynthetic enzyme does not always result in a successful increase in the levels of alkaloid production.…”
Section: Clarification Of the Molecular Basis Of The Iqa Biosyntheticmentioning
confidence: 93%
“…Recently, it has been reported that opium poppy transformed with constitutively expressed gene for codeinone reductase, showed a higher content of morphinan alkaloid [ 37 , 38 ]. Coptis japonica was modified to improve alkaloid yields by overexpressing the 3-hydroxy- N -methylcoclaurine-4- O -methyltransferase (4-OMT) gene, one of the key enzymes in BIAs biosynthesis in this species [ 39 , 40 ]. Overexpression of the Papaver somniferum berberine bridge enzyme (BBE) in Eschscholzia californica led to the accumulation of the end products benzophenanthridine alkaloids compared to controls [ 41 ].…”
Section: Working With Living Organisms: Biotechnological Approachementioning
confidence: 99%
“…Although plant engineering has been used to induce secondary metabolites accumulation [ 40 , 48 , 49 , 50 ], it is not easy to achieve the desired products because their biosynthesis are tightly regulated. For example, in most pathways, overexpression of one enzyme results in making subsequent reactions more limiting.…”
Section: Working With Living Organisms: Biotechnological Approachementioning
confidence: 99%
“…78) Overexpression of 4 0 OMT in a homologous host, the C. japonica plant, however, resulted in a marked increase in the amount of alkaloids, whereas transgenic C. japonica plants that overexpressed Cj4 0 OMT showed slower growth than the wild type. 79) Many experiments have indicated that the overexpression of other biosynthetic enzymes in various host plants has various effects, and thus suggest that more intensive studies of metabolic flow in various types of target-plant cells, are essential for continued progress in metabolic engineering, and especially to improve yields, through overexpression of rate-limiting enzymes. 73) Thus, cell culture systems offer another advantage in analyzing metabolic flux, since they are amenable to the application of stable isotopes.…”
Section: Metabolic Engineering In Cultured Cellsmentioning
confidence: 99%